Tahl?l al-Akh??’ al-Lughawiyah al-Kit?biyah f? Nu??? al-Hiw?r?t f? Barn?mij Tadr?b al-Lughah bi Ma?had al-Yusr? - Muflihat, Tantrie Aryani; Maslamah; Muhammad Nanang Qosim (El-Jaudah : Jurnal Pendidikan Bahasa dan Sastra Arab, 2024)
Writing skill is an important element that learners must master during the process of acquiring the Arabic language. Error analysis is one of the means on which applied linguistics and teaching Arabic to non-native speakers rely. The study aimed to find out the number of written language errors in dialogue texts in the language training programme at Al-Yusra Institute among ninth grade female students. The study used the descriptive-analytical approach to gather the requirements of the study from collecting, classifying, interpreting, and analysing the written language errors. The study produced 55 errors. 26 errors in grammatical errors, 8 errors in morphological errors, 10 errors in spelling errors, 2 errors in semantic errors, and 9 errors in lexical errors. The results of this research show that mastering grammar and vocabulary selection still requires more focus in the Arabic language learning process. These errors can be a reference to improve teaching methods to become more effective.